القطاع السياحي كبديل استراتيجي لدعم التنمية الاقتصادية في الجزائر - لمطوش, لطيفة; بوادو, فاطيمة (جامعة الوادي - University of Eloued, 2020)
ملخص: تعاني الجزائر كغيرها من البلدان الريعية من لعنة تسيير مواردها الناضبة خاصة مع التقلبات الحاصلة في أسعار النفط، لذا وجب عليها ايجاد بديل استراتيجي للدخل يعمل على استغلال مواردها خصوصا السياحية منها بشكل يضمن استدامتها، ولقد جاءت هذه الورقة البحثية لتسليط الضوء على دور القطاع السياحي في الجزائر كصناعة أولى ومساهم فعال في التنمية الاقتصادية والاجتماعية بالنظر للعوائد المالية المتأتية منه وما يوفره من مناصب شغل، تسعى من خلاله الجزائر للتخلص من مشاكلها الاقتصادية برؤية استراتيجية على المدى البعيد من خلال المخطط التوجيهي للتهيئة السياحية لآفاق سنة 2030. وقد توصلت الدراسة إلى أنه وبالرغم مما تملكه الجزائر من وجهات ومنتجات سياحية متنوعة إلا أن القطاع السياحي لا يزال يعاني من التهميش ونسبة مساهمته في الاقتصاد الجزائري ضعيفة مقارنة مع ما تملكه من امكانيات. Abstract: Algeria, like other exporting oil countries suffers from the curse of managing its own resources, especially with fluctuations in oil prices. Therefore, Algeria must find a strategic alternative revenue that exploits its resources, especially tourism in a way that ensures its sustainability. This paper highlights the role of the tourism sector in Algeria as a first industry and an active contributor to economic and social development in view of the financial returns it generates and the jobs it provides, through which Algeria seeks to eliminate its economic problems with a long-term strategic vision through the plan of configure tourism prospects for 2030. This study concluded that, despite the variety of tourism destinations and products in Algeria, the tourism sector is still suffering from marginalization, and the percentage of its contribution to the Algerian economy is weak compared with its possibilities.
TOURISM SECTOR AS A STRATEGIC ALTERNATIVE FOR ECONOMIC DEVELOPMENT IN ALGERIA
Keywords: سياحة ; التنمية المستدامة ; التنمية السياحية المستدامة ; مؤشرات السياحة مستدامة ; المخطط التوجيهي للتهيئة السياحية افاق 2030